Analytical modelling of force transmission in axially loaded RC columns with indirectly loaded jackets. (15th February 2019) - Minafò, Giovanni
Highlights: The compressive behaviour of RC columns with indirectly loaded external jackets is studied. Closed form solution is given for elastic behaviour of constituent materials. A mechanical-based step-by-step procedure is proposed for RC members with steel jackets, assuming proper constitutive laws. Comparisons are made with non-linear FE simulations and experimental data, showing good agreement. Abstract: Concrete and steel jacketing are common strengthening techniques for reinforced concrete (RC) columns subjected to axial loads. In the most of cases the external jacket is made leaving gaps between the strengthening layer and the slabs, avoiding to carry directly a portion of the load. In this way, the external jacket induces a confinement pressure on the inner column, and its beneficial effect is due to the increase of strength and ductility. However, shear stresses develop on the interface between the column and consequently, the external jacket can be considered indirectly loaded. It sustains a portion of the axial load, which depends by the value of the axial shortening, relative slippage between core and jacket and therefore by geometrical and mechanical features of the system. The evaluation of this effect is quite complex, since it depends from several parameters. This paper presents an analytical model able to predict the distribution of relative slips and shear stresses at interface in axially loaded RC columns reinforced with indirectly loaded jackets. Closed form expressions of maximum slip and stress distribution are obtained for linear elastic materials and formulation is extended to RC members via a step-by-step procedure allowing also to obtain the overall load-shortening curve. Results show the dependence of the compressive response from the interface's stiffness. The analytical solution is verified with results derived by non-linear finite element analyses, showing good agreement for different key parameters. Finally, comparisons with experimental data available in the literature are performed, proving the reliability of the model.